Socio-Economic Relations of Horticultural Farmers in the Agricultural Distribution System in Nagari Pandai Sikek, X Koto Sub-District (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study seeks to examine and analyze the socio-economic relationship carried out by horticultural farmers in the distribution of agricultural products, namely with toke. In this study using qualitative research methods descriptive type. Data collection techniques through observation, interviews and documentation with informant determination by purposive sampling. The results showed that farmers are related to toke, which is a distribution agent who buys farmers' agricultural products, in this relationship a pattern of dependence between farmers and toke, because farmers get guaranteed and guaranteed income. Trusting, emotional and honest relationships are strengths in marketing. Due to economic, and socio-cultural factors, farmers benefit economically and form farmer habits from a set of knowledge, cultural practices and behaviors that exist in an individual as a result of his interaction with the local environment. Juxtaposed with the theory of peasant rationality, the moral economic problems of peasants who have to struggle to live on the boundary line of subsistence. Farmers will use the concept of